PERBAIKAN KUALITAS DENGAN METODE RESPON PERMUKAAN PADA MESIN EXTRUDER DAN MESIN OVEN ANNELING DALAM PROSES PRODUKSI PRODUK ALUMINIUM COLLAPSIBLE TUBE 13,5x70/CE DI PT. EXTRUPACK - Andri Bagio Satrio; Melinda Latief (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2012)
PT Extrupack is one company that is engaged in the packaging industry aluminum tube that is often used as a packaging material for products - pharmaceuticals, cosmetics, toothpaste and others. In an effort to improve the quality of products it produces, PT Extrupack trying to improve existing production processes at this time that the number of defects that arise during the production process can be further minimized in number.First of all observations made on the production of 13.5 x 70/CE Collapsible Tube and search for the critical quality characteristics of this production process from product inspection standards in terms of variables there are several variables that have a low process capability that is high nozzle (Cp = 0.76) and flabbiness tube (Cp = 0.65), then this is the quality characteristics selected for further analysis. Of cause and effect diagram is known that the deviation is mainly due to long-run penyettingan engine is still done based on experience and trial and error. Therefore, design of experiments performed using the response surface method can be proposed for the optimum engine settings on the machine exturder affecting the response variable nozzle height and optimum setting for the machine anneling affecting the response variable softness tube.From the full factorial experiment and the results of data processing and analysis has been done, it is known that factors which significantly influence the response variable nozzle height is a factor B (Extrusion Pressure) and factor C (Levels of Zinc Stearate). With the response surface method to obtain the optimum setting Extruder machine that can be proposed is a factor A (Extrussion Speed) with the level 90mm/detik, factor B (Extrussion Pressure) with the level of 50 tons, and the factor C (Levels of Zinc Stearate) with the level 22.3%. As for the variable response of tube softness in mind that a significant factor is the factor A (temperature) and factor B (Old heating). Next by using the method of steepest Ascent and Central Composite Design to the proposed setting is optimum for engines Anneling Factor A (temperature) with the level of 523oC, Factor B (Old heating) with a value of 137 seconds and the level of factor C (Humidity) with values as low as 20% .From the results of the implementation of the proposed new setting can be seen that the characteristics of the process capability for high quality and softness nozzle tube after implementation is much better than before.